2004
DOI: 10.1103/physrevlett.93.017002
|View full text |Cite
|
Sign up to set email alerts
|

Shrinking Magnetic Vortices inV3Sidue to Delocalized Quasiparticle Core States: Confirmation of the Microscopic Theory for Interacting Vortices

Abstract: We report muon spin rotation measurements on the conventional type-II superconductor V3Si that provide clear evidence for changes to the inner structure of a vortex due to the delocalization of bound quasiparticle core states. The experimental findings described here confirm a key prediction of recent microscopic theories describing interacting vortices. The effects of vortex-vortex interactions on the magnetic and electronic structure of the vortex state are of crucial importance to the interpretation of expe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
43
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 35 publications
9
43
1
Order By: Relevance
“…[68][69][70] The same experiments find a significant increase of the amount of quasiparticle states in between vortices with the magnetic field. 69 It is proposed that different Andreev levels are formed in vortex cores of multiband superconductors, associated to different parts of the Fermi surface with varying gap size. The magnetic-fieldinduced disappearance of the smaller-sized superconducting gaps depletes core states created by smaller gaps.…”
Section: -3supporting
confidence: 48%
See 1 more Smart Citation
“…[68][69][70] The same experiments find a significant increase of the amount of quasiparticle states in between vortices with the magnetic field. 69 It is proposed that different Andreev levels are formed in vortex cores of multiband superconductors, associated to different parts of the Fermi surface with varying gap size. The magnetic-fieldinduced disappearance of the smaller-sized superconducting gaps depletes core states created by smaller gaps.…”
Section: -3supporting
confidence: 48%
“…This, in turn, gives core states with only large gaps associated Andreev bound states that are confined at a smaller length scale. 69 The definition of the vortex core radius is somewhat arbitrary 70 and depends on the particular experiment. It is found that, generally, the magnetic field produces a slight reduction of the coherence length ξ in conventional superconductors.…”
Section: -3mentioning
confidence: 99%
“…ξ is a measure of the vortex core size. Recently, we have demonstrated from µSR and thermal conductivity measurements on BCS superconductors 7,8 that the core size is dependent on the degree of localization of the quasiparticle bound core states. Thermal depopulation of the more spatially extended high-energy core states results in a shrinking of the core size with decreasing temperature.…”
Section: B Temperature Dependences Of λ and ξmentioning
confidence: 99%
“…(19) and integrating over s one obtains S in the form (18). Having the quantity S(H, ξ, T, ℓ) for both 3D (Fermi sphere) and 2D (Fermi cylinder), one can solve Eq.…”
Section: Fermi Cylindermentioning
confidence: 99%